The Relationship between Field Work Experience and Self-Efficacy on Students’ Work Readiness - Alimin, Lowalangi Wahyu Muji; Ningrum, Gres Dyah Kusuma (Lectura : Jurnal Pendidikan, 2025)
Vocational education plays a crucial role in preparing students for the workforce by integrating practical experience with personal development. This study aims to analyze the effect of Field Work Practice and Self-Efficacy on Work Readiness of SMK (Sekolah Menengah Kejuruan) Negeri 1 Singosari students. This study used a quantitative approach with an ex post facto design, chosen because it is appropriate to study existing conditions without direct manipulation. The sample consisted of 72 grade XII students of the Industrial Automation Engineering Department, representing the entire target population through saturated sampling. Data were collected using a validated and reliable questionnaire. Regression analysis showed that Field Work Practice and Self-Efficacy simultaneously had a significant effect on work readiness (R² = 0.769; p < 0.05). However, partially, only self-efficacy had a positive and significant effect (β = 0.980; p < 0.05), while Internship Experience had a positive effect but was not statistically significant (β = 0.150; p > 0.05). The insignificant results for Field Work Practice may be attributed to location variations and differences in the quality of guidance. In conclusion, these findings underscore the important role of self-efficacy in vocational education, suggesting that schools should implement targeted programs such as confidence-building workshops and structured mentoring to enhance students’ readiness for work.